Development of anti-cancer and anti-hypertensive nanodelivery systems using magnetite iron oxide-polymeric nanoparticles - Dorniani, Dena (2015)
Nanoscience and nanotechnology have received considerable attention due to their benefits to many areas of research and application such as pharmaceutical industry, medicine, electronics and tissue engineering. Much of nanoscience and nanotechnologies are concerned with producing new materials especially for use as diagnosis, and drug delivery systems. According to the World Health Organization and Cancer Research UK, the top two causes of death in the world are due to the hypertension (one of the primary risks factors for cardiovascular diseases) and different known cancers that affect humans. As such, different types of carriers have been used to design different anti-cancer and anti-heypertensive therapeutic and diagnostic agents. The new developing drug delivery system has capability in which the drugs can be released in a sustained manner over long periods of time into the targeted tissue. Therefore, it enable an almost constant level of drug to be kept in the bloodstream (by injection method) or delivering it to a specific region of the gastrointestinal tract, orally for treatment of cancers and cardiovascular diseases. In order to reduce the toxicity of uncoated magnetite nanoparticles and prevent their aggregation which occurs due to dipole-dipole attraction of magnetic particles different biocompatible polymers were used as a coating material. One of the polymer that was used as a coating material for nanoparticles is a natural polymer, chitosan. Due to NH3+ groups of chitosan, it can be attracted by by –OH- groups of iron oxide nanoparticles to inhibit the nuclear growth of iron oxide. The other polymer known as poly ethylene glycol (PEG) which is soluble in both polar and nonpolar solvents due to the presence of polar oxygen atom and nonpolar (CH2)2 group in it. Also, because of coating the nanoparticles with a neutral and hydrophilic compound such as PEG and polyvinyl alcohol (PVA), the circulatory half-life can be increased from minutes to hours or days. This study aimed at the synthesis and development of several anti-cancer and an anti-hyperthensive nanodelivery formulations using iron oxide nanoparticles (FNPs) coated with different biocompatible polymers such as chitosan (C), PEG and PVA, loaded with different active drugs namely gallic acid (GA), 6-mercaptopurine (MP) and perindopril erbumine (PE). A total of 7 nanocomposites based on the aforementioned anti-cancer drugs; GA and MP and anti-hyperthensive drug; PE were prepared by co-precipitation method to increase the residence time in the body via a sustained release formulation to increase the clinical efficacy. All the three (3) active drugs (GA, MP and PE) were integrated separately into iron oxide-chitosan and iron oxide-PEG to form 6 new nanocomposites; FCG, FCMP-D, FCPE, FPEGG, FPEGMP-2 and FPEGPE, respectively. The active drug gallic acid (GA) was also loaded onto iron oxide nanoparticles-polyvinyl alcohol (FNPs-PVA) to form FPVAG nanocomposite. The release behaviour of the drugs from the nanocomposites in human body simulated phosphate buffer solutions (PBS) of intercellular lysosomal pH 4.8 and human blood pH 7.4 was found to be of sustained manner. The release of the drugs from FCG, FCMP-D, FCPE, FPEGG, FPVAG, FPEGMP-2 and FPEGPE nanocomposites in human body simulated phosphate buffer solutions (PBS) of human blood pH 7.4 is 1600, 6300, 5631, 6905, 6594, 5520 and 4223 minutes respectively, compared to 1300, 2500, 2743, 5775, 3045, 4440 and 1231 minutes respectively, at pH 4.8 (human body simulated PBS of intercellular lysosomal). It was found that all the nanocomposites were more biocompatible compared to free drugs although the choice of coating materials as well as loading percentages of active drugs on the nanocarrier was found to be affected by the activity of the resulting materials. Cytotoxicity study of FCG nanocomposite shows greater anticancer activity as was seen in MCF7 cell lines than in HT29 cell lines. Also, after 72 hours of treatment, the FCG nanocomposite was not toxic to a normal human fibroblast (3T3) cell lines in the tested doses. The FCMP-D nanocomposites, shows better anticancer activity against leukemia cell lines (WEHI-3B) than FCMP and pure drug. The IC50 for the FCMP-D is 1.19 ± 0.45 μg/mL compared to 4.94 ± 0.76 μg/mL for FCMP nanocomposite after 72 hours post treatment exposed to 0.47-30 μg/mL concentrations. It was found that the FPEGG nanocomposite demonstrated higher anticancer effect on the breast cancer cell lines (MCF7) in almost all concentrations tested (0.78-25.0 μg/mL) compared to FPVAG nanocomposite. Anticancer activity of FPEGMP-2 nanocomposite was found to be slightly higher than FPEGMP-0.5 in a dose-dependent manner on the leukemic cell lines (WEHI-3B) after 72 hours of treatment exposed to 1.9-60 μg/mL concentrations. This may be attributed to the differences in the percentage of 6-mercaptopurine between the two nanocomposites. Also, MP which is loaded into the surface of FNPs-chitosan compared to FNPs-PEG nanocarrier with the same molar ratio, shows better cytotoxicity effect which is due to the role of chitosan. The whole study shows that, iron oxide nanoparticles had a negligible effect in normal and all cancerous cell lines tested in this study. It was found that between 70-100% of cells remaining viable from 0.47 μg/mL to 60.0 μg/mL concentrations. Thus, the cytotoxicity to cancerous cell lines are likely attributable to release of active drugs (GA and MP) from the nanocarrier rather than the effect of the carrier itself. Therefore, this study demonstrated that all the new nanocomposites show controlled release property of the active drugs, and therefore can be exploited for drug delivery system. Results from in vitro studies were found to be very encouraging to further conduct the in vivo studies of these novel nanocomposites in the future.